The Role of Price and Product Quality on Consumer Loyalty through Consumer Satisfaction as Intervening Variables (For Students Domiciled in Merjosari Village, Malang) - Nur Syahraini; Ridwan Basalamah; Eka Farida (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the regional financial performance of the Lembata district government in 2013-2017. This research is a case study with data collection using documentation techniques, and the data used is sectional data in the form of Realization of the Regional Income and Expenditure Budget of Lembata in 2013-2017. Furthermore, this data is analyzed using financial ratios, namely the degree of decentralization, constellation of regional dependency, regional financial independence ratio, regional tax effectiveness ratio, local tax efficiency ratio, harmony ratio, and growth ratio. The results of the study show that in general the financial performance of the district government is good. This is shown by the low average degree of decentralization, the very high regional financial dependency ratio, the regional financial independence ratio is still low with an intructive pattern, the effectiveness of the local tax ratio is quite efficient, the local tax efficiency ratio is efficient, the efficiency expenditure ratio, operating expenditure ratio the total expenditure dominates the expenditure allocation compared to the capital expenditure ratio to total expenditure, the ratio of local revenue growth and the ratio of income growth to positive growth, the ratio of operating expenditure growth, and the capital expenditure growth ratio experiencing positive growth.